ANALISIS TINGKAT KUALITAS PELAYANAN DENGAN MENGINTEGRASIKAN METODE SERVICE QUALITY KE DALAM METODE IMPORTANCE AND PERFORMANCE ANALYSIS (Studi Kasus : Cha - cha Milk Tea) - R. Abdul Jalal; Ibnu Jayamandau (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
This research is aimed to measure the satisfaction level of Cha-cha Milk Tea‟s service and also the attributes that are needed and used to be priority of improvement by management. The method used is Service Quality (SERVQUAL) which is integrated into Importance and Performance Analysis‟s method (IPA). Data obtained by distributing questionnaires to 80 respondents ofCha-cha Milk Tea‟scustomer. The results showed unsatisfactory levels of service satisfaction, because the satisfaction scores is less than 1. Attribute “Toilet yang bersih” is the attribute with the largest negative scores, and the other attributes which is be the priority of improvement are : “Karyawan yang selalu memberi salam dan sapa”, “Adanya iklan yang menarik minat pelanggan”, “Sarana parkir yang luas”, “Toilet yang bersih”, “Tersedianya pengharum ruangan”, and “Selalu mengedepankan layanan profesional”.